A method of reduction e-mails using replacement and repression. (11th December 2008) - Sakakibara, Atsushi; Atlam, El-Sayed; Morita, Kazuhiro; Fujita, Yasuhiko
E-mail systems are one of the most useful communication tools for business, education, etc., but missing e-mail information becomes a very serious problem. Therefore, it is important to retrieve the meaning of messages efficiently, that is to say, finding important portions from messages by changing pages are inefficient actions. This paper presents a method of reducing messages by keeping the meaning of massages. This solution is useful for small size devices such as PDA, handy phones and so on. The presented method defines replacement and repression patterns, but the text's meaning is sometimes altered. In order to solve this problem, this paper introduces a meaning distortion rate and the criterion of reducing texts uniformly. For the real time process, an extension of a string pattern-matching algorithm is discussed. From the simulation results by using reduction knowledge with 15, 000 patterns for e-mail, it turns out that the rate of reducing texts by the presented method is about 75%, the rate of keeping meanings of the original messages is 95% and the time of processing one mail becomes 0.1 ms.